Providing Nutrition for Residents of Tyumen during Great Patriotic War - K. A. Ankusheva; T. I. Bakulina (Научный диалог)
The article examines the problem of organizing centralized and additional food supply for the population during the Great Patriotic War, using the example of the rear city of Tyumen. The functioning of retail trade and the ration card system are studied. Examples of mutually beneficial cooperation between the city and the village in the context of the topic under consideration are provided. The authors characterize the public catering system, both for children and adults, as well as the organization of subsidiary farms and individual gardens. Attention is paid to food procurement and targeted assistance to those in need, as well as the participation of various categories of the population in this work, such as labor collectives, schoolchildren, etc. Conclusions are drawn about the main trends in the organization of food supply to the city’s residents. These include the efforts of central and local authorities to provide the population with the necessary minimum of food, proactive actions by city residents and entire enterprises to solve the food problem, and efforts to combat abuse. The relevance of the study is determined by the enduring importance of food security as an element of national security. The main sources of the work are materials from the newspaper “Krasnoe Znamya,” as well as documents from the archives of the region and the Tyumen Museum-Education Organization, some of which are being introduced into scientific circulation for the first time.